Flexible, ambipolar organic field-effect transistors based on the solution-processed films of octanaphthoxy-substituted bis(phthalocyaninato) europium. (April 2015) - Kong, Xia; Jia, Qi; Wu, Fanghua; Chen, Yanli
Abstract: A new sandwich-type bis(phthalocyaninato) europium complex [Pc(OAr)8 ]Eu[Pc(OAr)8 ] [Pc(OAr)8  = 2, 3, 9, 10, 16, 17, 23, 24-octanaphthoxy phthalocyanine], was synthesized and fabricated into organic field-effect transistors devices on a flexible plastic substrate by using a simple solution-based quasi–Langmuir–Shäfer method. Ambipolar transport has been obtained in [Pc(OAr)8 ]Eu[Pc(OAr)8 ]-based thin film transistors with the carrier mobilities to 0.10 cm 2  V −1  s −1 for holes and 0.01 cm 2  V −1  s −1 for electrons, respectively. The energy levels of the highest occupied molecular orbital (−4.63 eV) and the lowest unoccupied molecular orbital (−3.41 eV) were obtained based on electrochemical studies of this double-decker complex. These values just simultaneously meet the energy levels required for p -type and n -type natures of organic semiconductors, suggesting the ambipolar organic semiconducting nature of this double-decker complex. Organized film microstructures and J -type molecular stacking mode for the double-decker complex in the quasi–Langmuir–Shäfer film are revealed. This study constitutes the first attempt to fabricate low-cost, flexible ambipolar phthalocyanine-based organic field-effect transistors by using simple solution-processing methods. Graphical abstract: Flexible, ambipolar OFETs based on the solution-processed QLS films of a new bis(phthalocyaninato) europium complex are obtained with the carrier mobilities of 0.10 cm 2  V −1  s −1 for holes and 0.01 cm 2  V −1  s −1 for electrons, respectively. Highlights: A new sandwich-type bis(phthalocyaninato) europium complex was synthesized. First example to fabricate flexible OFETs by a simple quasi–Langmuir–Shäfer method. Good ambipolar transport for both holes and electrons has been obtained.